2017
DOI: 10.1007/978-3-319-59105-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Using Cluster–Context Fuzzy Decision Trees in Fuzzy Random Forest

Abstract: Part 3: Data Analysis and Information RetrievalInternational audienceCluster–Context Fuzzy Decision Tree is the classifier which joins C–Fuzzy Decision Tree with Context–Based Fuzzy Clustering method. The idea of using this kind of tree in the Fuzzy Random Forest is presented in this paper. The created ensemble classifier has similar assumptions to the Fuzzy Random Forest, but differs in the kind of used trees and all aspects connected with this difference. The quality of the created classifier was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In theory, the number of contexts should respond the number of object groups in the dataset. However, experiments performed in Gadomer and Sosnowski (2017) shown that sometimes it is possible to achieve better results with breaking that assumption. The division into contexts can be performed using any membership function.…”
Section: Cluster-context Fuzzy Decision Treesmentioning
confidence: 99%
See 2 more Smart Citations
“…In theory, the number of contexts should respond the number of object groups in the dataset. However, experiments performed in Gadomer and Sosnowski (2017) shown that sometimes it is possible to achieve better results with breaking that assumption. The division into contexts can be performed using any membership function.…”
Section: Cluster-context Fuzzy Decision Treesmentioning
confidence: 99%
“…The detailed description of C-fuzzy random forest with C-fuzzy decision trees was presented in Gadomer and Sosnowski (2016) and Gadomer and Sosnowski (2019). The other variant of C-fuzzy random forest, which uses Cluster-context decision trees, was presented in Gadomer and Sosnowski (2017).…”
Section: C-fuzzy Random Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…Some comparisons are given and analyzed in the work of Wang et al 8 It not only compares three algorithms but also applies the concept of degree of importance to build a fuzzy decision tree. Currently, the same group then applies clustering in the work of Gadomer and Sosnowski, 27 joining the C-FDT with the approach of context-based fuzzy clustering. 11 Big data is also one of the research branches in the fuzzy decision tree, and lots of novel methods are proposed such as big data-driven smart energy management, 12 indexing techniques, 13 semiautomagical fuzzy partition method, 14 modified Gini index fuzzy SLIQ decision tree algorithm, 15 Chi-FRBCS-BigData algorithm, 16 and multiobjective evolutionary algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…It tests this classifier with four datasets to compare the results and discuss the influence of randomness. Currently, the same group then applies clustering in the work of Gadomer and Sosnowski, joining the C‐FDT with the approach of context‐based fuzzy clustering. Both datasets of discrete and continuous features test this approach and show good results.…”
Section: Related Workmentioning
confidence: 99%